PERENCANAAN ALAT PEMBERI ISYARAT LAMPU LALU LINTAS (APILL) PADA PERSIMPANGAN JALAN PULAU GALANG, JALAN TAMAN PANCING DAN JALAN TUKAD BARU - I Wayan Putra Praja Utama; A.A. Gede Sumanjaya (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
ABSTRACT The junction of Pulau Galang streets, Jalan Pancing streets and Tukad Baru streets is one of the intersections that traffic flow is quite solid. If seen from the congestion that often occurs at this intersection, it can be seen that it needs an application of Traffic Management, the installation of traffic lights (APILL). Therefore, the purpose of writing this final task, among others, is to analyze the performance of intersection intersection (current state) and plan traffic management using traffic light. To analyze the performance of the intersection and to plan the setting of the intersection, first, there are surveys to get incoming data. The data can be primary data obtained directly from the source, or secondary data obtained not from the source directly, for example data obtained from relevant agencies. Analysis data were used the method of Manual Capacity Jalan Indonesia (MKJI, 1997). From the analysis result, it can be found that the performance of intersection at peak hour of day and afternoon, has the capacity (C) peak at 2566 smp/hour and the peak of afternoon 2460 smp/hour, the saturation degree (DS) at peak hour of 0.96 and peak afternoon hours 1, the average delay of the intersection (D) at the peak hour of 18.35 sec/pc, and the peak hour of afternoon 20 second/smp, the queue probability (QP%) at the peak hour of 73 - 36% afternoon, and the peak hour of the afternoon 79 - 40%, service level C for peak hour day and afternoon. To fix and overcome the problem at the intersection then the next thing is done planning the traffic signs (traffic light). The selected intersection setting type is an intersection setting with a two-phase signal, since the delay is relatively small, entering level B at the service level service. Compared with the three-phase signal regulator with the initial green determination on the major or main road approach and the four-phase signal arrangement with the current departing one by one on each approach, the service level is greater than the two-phase signal setting. Keyword: APILL, capacity, saturation degree, delay the intersection